Desarrollo de un Sistema Web y móvil para la Veterinaria "PATITAS VET" ubicada en el cantón Latacunga provincia de Cotopaxi. - Bastidas Arévalo, Jessenia Stefanny (2022)
The present project carried out at the "Patitas VET" veterinary clinic in the city of Latacunga, has the objective of developing a web and mobile application focused on booking appointments and order management, in which it was identified that due to the pandemic it has caused problems such as the agglomeration of people in the premises, either to schedule an appointment or for any query, consequently the lack of a system that allows clients to have the necessary knowledge of the services provided by the veterinarian as well as the lack of a system was taken as the main problem. as well as the products that are being implemented in the veterinary medicine. Therefore, for the development process of the applications, the information was collected applying methodologies, tools and techniques, such as interviews, surveys and observation sheets for the identification of needs and obtaining the requirements, for this reason the web application is created with the programming languages Django, HTML and CSS, for the development of the mobile application Kotlin, Javascript and POSTGRESSQL as a database while the SCRUM methodology is used for the management and development of different artifacts for the applications mentioned above. The application has an administrator who will be the owner of the veterinary who will be in charge of managing clients, pets and products to be offered, management of appointment reservations, and in this way comply with the objective of creating an application for the Appointment booking and order management for Patitas "VET" veterinary in the city of Latacunga.